Patterns of Student Management in the OPPM Student Shop Cooperation Activities - Syarifah Syarifah; Nurul Salis Alamin; Riza Ashari; Idam Mustofa; Ahmad Saifulloh (Jurnal Penelitian Pendidikan, 2026)
Through activities in the Student Shop Cooperation Section of the Modern Islamic Boarding School Student Organization (OPPM) of Pondok Modern Darussalam Gontor Putri 1, this study seeks to examine how female students develop independent character. This study employs a descriptive design and a qualitative methodology. Participatory observation, semi-structured interviews, and documentation studies were used to gather data from research subjects, which included administrators, Cooperation advisers, and student shop Cooperation members. Throughout the phases of data condensation, data display, conclusion drawing, and verification, data analysis was done interactively. The study's findings show that an organized student management pattern, which includes organizing, planning, carrying out, and assessing Cooperation activities, helps female students develop independent character. The development of emotional, financial, intellectual, and social independence is facilitated by female students' participation in Cooperation management. The Islamic boarding school's student shop Cooperation serves as both an economic entity and a vehicle for character education grounded in ongoing habituation and real-world experiences. According to the study's findings, integrating student management with Cooperation learning activities is a successful tactic for helping female students develop independent personalities. The results of this study are anticipated to have both practical consequences for the administration of student organizations centered on character formation and theoretical contributions to the advancement of character education studies in Islamic boarding schools.